Compliance with NICE guidelines when commissioning varicose vein procedures. Issue 6 (29th August 2018) - Carradice, D.; Forsyth, J.; Mohammed, A.; Leung, C.; Hitchman, L.; Harwood, A. E.; Wallace, T.; Smith, G. E.; Campbell, B.; Chetter, I.
Abstract : Background: Varicose veins impair quality of life and can lead to chronic leg ulcers. National Institute for Health and Care Excellence (NICE) guidelines (CG168) set out evidence‐based standards for patient management. In England, Clinical Commissioning Groups (CCGs) fund NHS care within their locality. The objective of this study was to evaluate CCGs' commissioning policies and compare them with CG168. Methods: Searches were made for the published policies of all 206 English CCGs. They were reviewed for compliance with NICE guidelines and the associated quality standard. Areas of disagreement were analysed for themes. Results: Some 203 CCGs (98·5 per cent) had a published policy and 190 (93·6 per cent) of these were published after publication of CG168. Only 73 of the policies (36·0 per cent) were compliant with CG168. Treatment was restricted on the basis of clinical disease severity in 119 CCGs (58·6 per cent); 29 (14·3 per cent) stipulated delay of treatment using a 'trial' of conservative treatment; 22 (10·8 per cent) used lifestyle‐related factors such as BMI and smoking status to ration treatment. Treatment was commissioned for uncomplicated symptomatic varicose veins in 87 CCGs (42·9 per cent), but some applied additional rationing mechanisms; 109 CCGs (53·7 per cent) would treat oedema, 183 (90·1 per cent) would treat skin and soft tissue damage, 202 (99·5 per cent) healed ulceration, and all would allow active ulcers to be treated. Discussion: The majority of CCGs in England have commissioning policies that contradict NICE guidelines. Rationing strategies include disease severity, delay and patient lifestyle‐related factors, creating unwarranted geographical variation for varicose vein treatment, disregarding the NHS Constitution for England, and perhaps leading to an increase in costly treatment of chronic complications in the long term. Abstract : There is widespread conscious rationing of varicose vein treatment by Clinical Commissioning Groups in England. This is in contradiction of National Institute for Health and Care Excellence (NICE) guidelines and the NHS constitution. Rationing despite NICE guidance